Proteomic responses of oceanic Synechococcus WH8102 to phosphate and zinc scarcity and cadmium additions - Cox, Alysia; Saito, Mak (Frontiers in Microbiology, 2013)
Synechococcus sp. WH 8102 is a motile marine cyanobacterium isolated originally from the Sargasso Sea. To test the response of this organism to cadmium (Cd) -generally considered a toxin- cultures were grown in a matrix of high and low zinc (Zn) and phosphate (PO43-) and were then exposed to an addition of 4.4 pM free Cd2+ at mid-log phase and harvested after 24 h. Whereas Zn and PO43- had little effect on overall growth rates, in the final 24 h of the experiment three growth effects were noticed: i) low PO43- treatments showed increased growth rates relative to high PO43- treatments, ii) the Zn/high PO43- treatment appeared to enter stationary phase, and iii) Cd increased growth rates further in both the low PO43- and Zn treatments. Global proteomic analysis revealed that: i) Zn appeared to be critical to the PO43- response in this organism, ii) bacterial metallothionein (SmtA) appears correlated with PO43- stress-associated proteins, iii) Cd has the greatest influence on the proteome at low PO43- and Zn, iv) Zn buffered the effects of Cd, and v) in the presence of both replete PO43- and added Cd the proteome showed little response to the presence of Zn. Similar trends in alkaline phosphate (ALP) and SmtA suggest the possibility of a Zn supply system to provide Zn to ALP that involves SmtA. In addition, proteome results were consistent with a previous transcriptome study of PO43- stress (with replete Zn) in this organism, including the greater relative abundance of ALP (PhoA), ABC phosphate binding protein (PstS) and other proteins. Yet with no Zn in this proteome experiment the PO43- response was quite different including the greater relative abundance of five hypothetical proteins with no increase in PhoA or PstS, suggesting that Zn nutritional levels are connected to the PO43- response in this cyanobacterium. Alternate ALP PhoX (Ca) was found to be a low abundance protein, suggesting that PhoA (Zn, Mg) may be more environmentally relevant than PhoX.